Let f : R → R be defined by f ( x ) = x 3 + 3 x + 1 and g be the inverse of f . If the value of g ′ ′ ( 5 ) is equal to b − a , where a and b are coprime positive integers, find the value of a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
good work .
simply brilliant!! ⌣ ¨
Nice problem ! :) Upvoted.
Did the same! Nice!
We note that since f ( 1 ) = 5 we have g ( 5 ) = 1 . Also, since g ( x ) is the inverse of f ( x ) it must satisfy: x = g ( x ) 3 + 3 g ( x ) + 1 Using implicit differentiation, solving for g ′ ( x ) , and then evaluating at x = 5 gives us: 1 g ′ ( x ) g ′ ( 5 ) = 3 g ′ ( x ) g ( x ) 2 + 3 g ′ ( x ) = 3 ( g ( x ) 2 + 1 ) 1 = 6 1 Using implicit differentiation again, solving for g ′ ′ ( x ) , and then evaluating at x = 5 gives us: 0 g ′ ′ ( x ) g ′ ′ ( 5 ) = 6 ( g ′ ( x ) ) 2 g ( x ) + 3 g ′ ′ ( x ) g ( x ) 2 + 3 g ′ ′ ( x ) = − g ( x ) 2 + 1 2 ( g ′ ( x ) ) 2 g ( x ) = − 3 6 1 Therefore the solution is a + b = 3 7 .
Conceptual way can sometime be an alternative to genuine way:
1 2 3 |
|
We must have consciousness in mind to apply the above method.
a + b = 1 + 36 = 37
Answer: 3 7
Problem Loading...
Note Loading...
Set Loading...
g ( x ) = f − 1 ( x ) f − 1 ( f ( x ) ) = x g ( f ( x ) ) = x
Differentiating
g ′ ( f ( x ) ) ∗ f ′ ( x ) = 1
g ′ ( f ( x ) ) = f ′ ( x ) 1 ....... ( 1 )
Also f ( 1 ) = 5 . u can check that by equation f ( x ) = 5
On again differentiating ( 1 )
g ′ ′ ( f ( x ) ) = ( f ′ ( x ) ) 3 − f ′ ′ ( x )
f ′ ( x ) = 3 x 2 + 3 a n d f ′ ′ ( x ) = 6 x
g ′ ′ ( f ( 1 ) ) = ( f ′ ( 1 ) ) 3 − f ′ ′ ( 1 )
g ′ ′ ( 5 ) = ( 6 ) 3 − 6
g ′ ′ ( 5 ) = 3 6 − 1
Do upvote